Evaluasi Website E-Commerce Bukalapak Menggunakan Webqual 4.0 Dan Importance Performance Analysis (IPA) - Fahroz Dwi Pratiwi; Pratama, Arista; Suryanto, Tri Lathif Mardi (E-Jurnal Universitas Samudra, 2025)
The rapid development of information and communication technology (ICT) has driven a shift in business strategies from conventional marketing to digital marketing, with e-commerce becoming an increasingly popular form of trade. The utilization of e-commerce in Indonesia shows great potential for further development. One key technology in e-commerce is the website, and Bukalapak is one of the e-commerce platforms that relies on its website for product marketing. To remain competitive and enhance user satisfaction, Bukalapak needs to focus on and improve the quality of its website. This study aims to identify the priority indicators that need improvement on Bukalapak's website based on the Webqual 4.0 quality dimensions and Importance Performance Analysis (IPA). The research method uses purposive sampling with 400 respondents who are Bukalapak users. The gap analysis results show that the performance quality of Bukalapak's website does not meet user expectations, with negative results in the variables of Usability Quality (-0.0118), Information Quality (-0.105), and Service Interaction Quality (-0.10125). The IPA quadrant analysis reveals three main indicators that need improvement: UQ6, IQ11, and IQ14. Additionally, there are several indicators with low priority for improvement located in quadrant III, namely UQ1, UQ4, IQ10, IQ13, SI16, SI20, and SI22. This study provides important insights for Bukalapak to improve the quality of its website to meet user expectations. Keywords: E-commerce Bukalapak, Webqual 4.0, Importance Performance Analysis (IPA), Gap Analysis (GAP).